From welfare to lawfare: Environmental suffering, neighbour disputes and the law in UK social housing. (June 2018) - Koch, Insa
Social housing authorities in the UK frequently invoke a language of 'anti-social behaviour' and neighbour nuisance in dealing with disputes between tenants. But this language fails to recognise the poor environmental conditions that cause disputes between tenants in the first place. An ethnographic analysis of neighbour disputes identifies a double move from a politics of welfare to one of lawfare: just as housing providers shift the blame onto individual tenants for tenants' perceived failure to act in socially appropriate manners, so tenants end up calling for more policing and tougher neighbourhood control. This politics of lawfare not only places a moral economy of blame at its core but further undermines the possibilities of transforming environmental suffering into redistributive struggles.